2019
DOI: 10.1021/acs.est.9b01562
|View full text |Cite
|
Sign up to set email alerts
|

Variations, Determinants, and Coexposure Patterns of Personal Care Product Chemicals among Chinese Pregnant Women: A Longitudinal Study

Abstract: Exposure to mixtures of personal care product chemicals (PCPCs) is commonplace among the Chinese population; yet, limited data are available on the variations, determinants, and coexposure patterns of PCPCs, particularly among pregnant women at multiple time points during gestation. Here, we measured concentrations of 11 most common PCPCs (five parabens, five benzophenones, and triclosan) in 2823 urine samples collected from 941 pregnant women over three trimesters. Based on the quantification results, we calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…In total, 17 studies describing temporal variability in urinary excretion of parabens in general population (Dewalque et al, 2015;Engel et al, 2014;Huang et al, 2021;Kim et al, 2020b;Koch et al, 2014;Nishihama et al, 2018;Pollack et al, 2016;Sakhi et al, 2018;Smith et al, 2012;van der Meer et al, 2021), pregnant women (Casas et al, 2018;Guidry et al, 2015;Li et al, 2019b;Meeker et al, 2013a;Philippat et al, 2013;Vernet et al, 2018;Yazdy et al, 2018) and children (Casas et al, 2018;Kim et al, 2020b) were retrieved from the literature search. ICCs for two parabens (MeP and PrP) were reported in all studies.…”
Section: Variability In Paraben Concentrationsmentioning
confidence: 99%
“…In total, 17 studies describing temporal variability in urinary excretion of parabens in general population (Dewalque et al, 2015;Engel et al, 2014;Huang et al, 2021;Kim et al, 2020b;Koch et al, 2014;Nishihama et al, 2018;Pollack et al, 2016;Sakhi et al, 2018;Smith et al, 2012;van der Meer et al, 2021), pregnant women (Casas et al, 2018;Guidry et al, 2015;Li et al, 2019b;Meeker et al, 2013a;Philippat et al, 2013;Vernet et al, 2018;Yazdy et al, 2018) and children (Casas et al, 2018;Kim et al, 2020b) were retrieved from the literature search. ICCs for two parabens (MeP and PrP) were reported in all studies.…”
Section: Variability In Paraben Concentrationsmentioning
confidence: 99%
“…Results of another study showed a significant negative association of physical activity with urinary concentrations of parabens [27]. However, positive associations have been reported between urinary MP and BP concentrations and the physical activity level [58]. The mechanism of the effect of intensity of physical activity on the increase or decrease of paraben excretion from the body is not well known.…”
Section: Discussionmentioning
confidence: 98%
“…The association between housing renovation exposure and CHD may be attributed to organic pollutants and other volatile contaminants being released from decoration materials. According to a prior study, women whose homes had been decorated in the previous three years had higher urinary benzophenone concentrations than women whose homes had not been decorated [23]. Several studies have revealed that maternal occupational exposure to organic solvents, such as acetone, toluene, xylene, and Stoddard solvent or Chlorinated solvents potentially increased the overall risk of CHD and other system anomalies [8][9][10][11].…”
Section: Discussionmentioning
confidence: 99%